ANALISIS KUALITAS SUMBER DAYA MANUSIA DAN PENGARUHNYA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN PELALAWAN - Freshka Hasiani. S; Yusni Maulida; Lapeti Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Conceptually development is all efforts will be undertaken in a planned manner in making changes with the main objective to improve and enchace quality of life, increasing and improving the quality of human welfare. Qualifed human resources provide or excellent effect when used appropriately. Benefits will be useful for the community and the state it self. Human resources is essential for developed countries and developing countries. The purpose of this study was to determine the effect of human resources to economic growth in the regency of Pelalawan. Methods of data analysis using linear regression multiple analys.This location of this research is the regency. This locatian was chosen because Pelalawan progressing economic growth from year to year. The method used to discuss this problem is by using a quantitative method of multiple linear regression model with SPSS, to determine the relationship variable quality of human resources and variable ecinomic growth. The results of data analysis in the study shows that the results of multiple linear regression with the count of value f 38,573, and 4,757 while the value of f tables. Therefore, the value ftable > fcount , it can be concluded that Ho is rejected or in other word, life expetancy, the old school and percapita income average of simultaneusly significant effect on economic growth in the Pelalawan Regency.Keyword : Quality of human resources and economic growth.